DEVELOPING MARKETING STRATEGIES BASED ON PARENTSâ BEHAVIOR TO INCREASE WILLINGNESS TO BUY CHILDREN EDUCATIONAL EVENT: A CASE STUDY OF FULOLA - Agustina, Nadia
Based on the Programme for International Student Assessment (PISA) results in 2018, the quality of education in Indonesia is still underdeveloped compared to other international countries. However, Indonesia has the potential to achieve the Sustainable Development Goals by improving the quality of education. The fact shows children who use interactive learning media get 84.83% higher results than other children. As a startup engaged in children's education, Fulola offers innovation for interactive learning in the form of children's educational events that can hone multiple intelligences. Unfortunately, based on the pilot event that Fulola held in February 2023, parents do not have the willingness to buy this event. Therefore, this study aims to explore the factors that influence parents in choosing children's educational events as a basis to provide marketing strategy recommendations to increase parents' willingness to buy. This research was conducted using a qualitative method through semi-structured interviews with high economic-class parents who live in Bandung and have previous experience participating in children's educational events. Data were analyzed using the coding method. The result show factors that influence customer behavior starting from Culture, Social, Personal, and Psychological. In addition, the marketing strategy that will be proposed based on customer behavior will be made in the form of 7Ps which consist of Product, Price, Place, Promotion, People, Process, and Physical Evidence. Hopefully, the results can contribute to making Fulola become a sustainable startup that gives impacts for the economy and education in Indonesia.